Fiscal rules and compliance expectations: Evidence for the German debt brake - Friedrich Heinemann; Eckhard Janeba; Christoph Schröder; Frank Streif (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Fiscal rules have become popular to limit deficits and high debt burdens in industrialized countries. A growing literature examines their impact based on aggregate fiscal performance. So far, no evidence exists on how fiscal rules influence deficit expectations of fiscal policy makers. In the context of the German debt brake, we study this expectation dimension. In a first step, we introduce a simple dynamic model in an environment characterized by the lagged implementation of a new rule. Lagged implementation characterizes the setup of the German debt brake and raises credibility issues. In a second step, we analyze a unique survey of members of all 16 German state parliaments and show that the debt brake's credibility is far from perfect. The heterogeneity of compliance expectations in the survey closely corresponds to our theoretical predictions regarding states' initial fiscal conditions, specific state fiscal rules and bailout perceptions. In addition, there is a robust asymmetry in compliance expectations between insiders and outsiders (both for in-state vs out-of-state politicians and the government vs opposition dimension), which we attribute to overconfidence rather than noisy information. These results suggest that national fiscal rules can be strengthened through nobailout rules, sustainable initial fiscal conditions and complementary sub-national rules.
urn:nbn:de:bsz:180-madoc-368658
Keywords: H6; H7; 330; Budget Deficits; Debt Brake; Credibility; Survey; Fiscal Rules